DEPICTION OF HINDU ICONOGRAPHY IN THE PAINTINGS OF THOTA VAIKUNTAM - Kumar, Banti; Mushtaq, Waseem (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The history of a human being is also the history of who or why or how human beings have worshipped something that they believed was more powerful than them. The history of human being is also the history of artists as how they have imagined, depicted or visualized this superpower. For instance, in the Indus Valley Civilization, we find that humans made clay idols which may have been worshipped, for instance, in the form of Mother Goddess and Pashupati Nath. Across prehistoric, ancient and medieval periods, as the circumstances of human life changed, so did the nature of worshiping and the nature of art. This act of worship gave rise to some of the greatest religions in the world with their dedicated sacred text, rituals, followers, and patronage. Each religion had a distinct and unique equation with art and it was based on this equation that it became possible to study and interpret a work of art. This approach of study or interpretation was later classified as iconography. The present paper aims to locate the presence of Hindu iconography in modern India with special reference to the paintings of Thota Vaikuntam, who is known for drawing extensively from the iconographic representations of Shiva, Ganesh, and Krishna.